Fibrinogen Bonn (p. Arg510Cys) in the Aα-Chain Is Associated with High Risk of Venous Thrombosis - Ivaškevičius, V.; Biswas, A.; Singh, S.; Stulpinaitė, U.; Reda, S.; Rühl, H.; Pezeshkpoor, B.; Pavlova, A.; Oldenburg, J. (Hämostaseologie, 2023)
Introduction Inherited dysfibrinogenemia is a qualitative defect of fibrinogen caused by various mutations among three fibrinogen genes. Dysfibrinogenemia can be associated with an increased risk of thrombosis, bleeding, or both. Here, we report a 36-year-old female with dysfibrinogenemia who experienced two successful pregnancies under thromboprophylaxis after cerebral venous sinus thrombosis (CVST).Patients and Methods In addition to plasmatic coagulation tests, fibrinogen genes FGA, FGB, and FGG were screened using direct genomic DNA sequencing. The structural-functional implications of the detected mutation were analyzed in silico.Results Inherited dysfibrinogenemia was diagnosed in an index patient after CVST in a risk situation. Anticoagulation with warfarin was stopped after 12 months when the first pregnancy was planned. Pregnancy and spontaneous delivery (2020) was uncomplicated. A second pregnancy was interrupted because of acute cytomegalovirus infection and the third pregnancy was successful in 2022. Pregnancies were accompanied by thromboprophylaxis with enoxaparin 40 mg once daily until 6 weeks postpartum. Substitution of fibrinogen has not become necessary in the index patient so far. Genetic analysis revealed a novel missense mutation (p. Arg510Cys) in the FGA gene (“fibrinogen Bonn”) in the index patient, as well as an asymptomatic sister, and their father who experienced recurrent pulmonary embolism. Surface exposure of wild-type Arg510 suggested the mutated Cys510 to form nonnative disulfide bonds with surface-exposed reactive cysteines from other plasma proteins like albumin leading to formation of aggregates and impaired fibrinolysis.Conclusions Fibrinogen Bonn might be associated with an increased risk of thrombosis, possibly due to impaired polymerization.
Keywords: dysfibrinogenemia; thrombosis; genetics; pregnancy; anticoagulation